Les Caisses d’épargne face à l’avènement d’un groupe bancaire universel : le changement organisationnel entre ingénierie managériale de la mémoire et attachement au passé - Julien Tassel (Conserveries Mémorielles)
Organisational change is usually considered from a management or an implementation point of view. This approach, as operational as it may be, ignores the relationship to memory and the past generally, which is fundamental in order to understand changes.Based on ethnographic field studies carried out from 2003 and 2007 at a major financial institution (Caisse d'Epargne Group), this article purports to shed light on certain memory-based challenges induced by change: difficulties to recognise the company as it evolves, managerial efforts to link the current situation with the past, which has been altered by the changes, conducts of staff members influenced by a willingness to uphold the original mission of the organisation.